2017
DOI: 10.1186/s12889-016-3915-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with male involvement in reproductive care in Bangladesh

Abstract: BackgroundMen’s active involvement in reproductive healthcare has shown to be positively associated with maternal and child health outcomes. Bangladesh has made appreciable progress in its pursuance of maternal mortality related goals in the framework of the MDGs. However, there remains a lot to be accomplished to realise the long-term goals for which active participation of male counterparts in reproductive care is crucial. Therefore, the objective of the present study was to investigate factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 37 publications
10
70
2
1
Order By: Relevance
“…These findings differ from a Bangladesh study of male involvement in reproductive health care, which showed that residence, education, and source of information were significant predictors on maternal health issues. 19 On the other hand, our finding of geographical zone and wealth quintile as significant predictors for modern contraceptive use was consistent with a finding of a Nepal study. 28 Men's involvement in women's sexual and reproductive health was a significant predictor of a positive health outcome for their partners and children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings differ from a Bangladesh study of male involvement in reproductive health care, which showed that residence, education, and source of information were significant predictors on maternal health issues. 19 On the other hand, our finding of geographical zone and wealth quintile as significant predictors for modern contraceptive use was consistent with a finding of a Nepal study. 28 Men's involvement in women's sexual and reproductive health was a significant predictor of a positive health outcome for their partners and children.…”
Section: Discussionsupporting
confidence: 92%
“…17 In rural areas of Myanmar, use of contraception was higher among wives who discussed contraception with their spouse argued that men's active involvement in reproductive health is positively associated with maternal and child health outcomes. 18,19 Greene and Barker advised researchers, policymakers, and program managers to give attention to male involvement in family health decisionmaking. 20 Therefore, shared responsibility of both men and women in reproductive health is an increasingly important issue.…”
Section: Introductionmentioning
confidence: 99%
“…From each article the following data have been extracted: study purpose, design, sample, and findings (Table 1). [6] Results showed that men's intention to discuss birth control is affected by attitudes, norms and self-efficacy -The more strongly men endorsed a traditional masculinity sexual script, are less likely intend to discuss birth control survey Online survey. Participants were men aged 18 -25.…”
Section: Resultsmentioning
confidence: 99%
“…Men (15 - [19] Then, authors compared articles to identify themes. Review articles show that law percentage of men involved in family planning practices [6]. From women perspectives men were seen as an obstacle and never enabled them to plan their next pregnancy [13].…”
Section: Resultsmentioning
confidence: 99%
“…Like all other south Asian nations, widespread poverty, poor healthcare infrastructure, inequality in access to care, and low health literacy constitute some of the major causes of underutilization of essential maternal healthcare services (e.g. antenatal care, professional services for childbirth) that translate to higher burden of MCM, which is recognised as a serious public health problem in the country [1,3,4]. Over the course of past few decades, the Ministry of Health and Family Welfare (MoHFW) has developed and implemented strategies for tackling high MCM rates through programmatic intervention within national (Population and Health Policy), international (Millennium Development Goals, MDG-5) [5] and joint (Maternal and Neonatal Health Initiatives in Bangladesh) [6] policy frameworks.…”
Section: Introductionmentioning
confidence: 99%